2022
DOI: 10.11606/s1518-8787.2022056003908
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy in Southern Brazil: prevalence, trend, and associated factors

Abstract: OBJECTIVE To identify and analyze the prevalence, trend, and factors associated with episiotomy in Rio Grande, in the state of Rio Grande do Sul, Southern Brazil. METHODS A single, standardized questionnaire was applied to all pregnant women, residents in the municipality of Rio Grande, who had children in local hospitals between January 1 and December 12 of the years 2007, 2010, 2013, 2016 e 2019. Demographic and socioeconomic characteristics were investigated, as well as the assistance received during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…Isso foi reafirmado segundo o artigo (Lucena et al, 2023), onde este procedimento é observado em 75% dos casos nas primíparas. De acordo com (Cesar et al, 2022) isso ocorre devido a menor elasticidade da musculatura perineal.…”
Section: Não Foi Analisado No Estudounclassified
“…Isso foi reafirmado segundo o artigo (Lucena et al, 2023), onde este procedimento é observado em 75% dos casos nas primíparas. De acordo com (Cesar et al, 2022) isso ocorre devido a menor elasticidade da musculatura perineal.…”
Section: Não Foi Analisado No Estudounclassified
“…Especificamente, ao abordar a saúde mental materna, estudos contemporâneos mostram a correlação entre aspectos sociodemográficos e Transtorno Mental Comum (TMC) (Quadros et al, 2020). A experiência da maternidade, por si só, conta de um momento significativo do ciclo reprodutivo e exige da mulher e dos familiares reestruturações e reajustamentos (Silva et al, 2020;Silva et al, 2022). O panorama que se pretende abordar neste estudo envolve novas configurações a partir da inserção de um contexto pandêmico ou pós-pandêmico (incluindo o distanciamento social) no desenvolvimento das famílias: mulher versus mãe, versus filhos, versus trabalho, versus família, versus cuidar do lar, versus cuidar de si própria, entre outras.…”
Section: Introductionunclassified
“…Episiotomy is opted in case of emergencies during the second stage of labor such as fetal distress, obstructed labor, and delayed progress of labor due to tight perineum [3][4][5]. This procedure is highly opposed due to the lack of scientific evidence of its benefits, especially when opted as a routine [6]. Several studies have reported that episiotomy promotes bleeding and injury in the perineal region, promotes sphincter trauma, causes bowel incontinence and flatulence, and prolongs postpartum pain, among other complications [1-6].…”
mentioning
confidence: 99%
“…Several studies have reported that episiotomy promotes bleeding and injury in the perineal region, promotes sphincter trauma, causes bowel incontinence and flatulence, and prolongs postpartum pain, among other complications [1-6]. There are different types of episiotomy incisions; however, the most commonly recommended and safest type is mediolateral episiotomy, in which the incision is made in the midline but directly downward and then laterally away from the rectum [1,2,6].In Yemen, data related to episiotomy, including its prevalence and frequency of complications, are sparse [7]. This study aimed to identify and analyze the prevalence, clinical profile, and complications of episiotomy among women who delivered at the Asha'ab Obstetric Emergency Center, in Aden city, Yemen.…”
mentioning
confidence: 99%
See 1 more Smart Citation